If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2a + 36 = 3a + 48 Reorder the terms: 36 + 2a = 3a + 48 Reorder the terms: 36 + 2a = 48 + 3a Solving 36 + 2a = 48 + 3a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3a' to each side of the equation. 36 + 2a + -3a = 48 + 3a + -3a Combine like terms: 2a + -3a = -1a 36 + -1a = 48 + 3a + -3a Combine like terms: 3a + -3a = 0 36 + -1a = 48 + 0 36 + -1a = 48 Add '-36' to each side of the equation. 36 + -36 + -1a = 48 + -36 Combine like terms: 36 + -36 = 0 0 + -1a = 48 + -36 -1a = 48 + -36 Combine like terms: 48 + -36 = 12 -1a = 12 Divide each side by '-1'. a = -12 Simplifying a = -12
| (-1+(6-3*(-3)))*5= | | 20=2(3x+1)+4x | | 19-3w=14+2x | | 4x-4y+z=4 | | 115/4= | | -19x+6=9 | | (-1+(6-3x(-3)))*5= | | 7s+3=15-5s | | x+17+8=-25 | | 91/3x5 | | (K-1)x^2+4k-1=(3+4k)x | | 7y-20=2y | | 3x-2(2x+5)=4 | | 18-4(2x-2b)=5b+2x | | 2(y-3)=2x-8 | | 7st+4t(t+s+4)-9t= | | 2.50+1.5(m-1)=17.50 | | 110d=115d+45 | | 4/6=x/11 | | 13r-39=10r | | 6x+5x-x= | | 65+k=8 | | 9x-5-14=17 | | (x-2)2=49xiswhat | | y=x^2-6x+9forx | | y=x^2-6y+9 | | 14lnx=17 | | 585=X^2 | | x+17+8=25 | | 3x(2x+40)=180 | | 5y^2+10y-120=0 | | 6(2x+y)= |